Prediction of Late Enophthalmos Using Preoperative Orbital Volume and Fracture Area Measurements in Blowout Fracture. Issue 7 (October 2017) - Choi, Su Hyun; Kang, Dong Hee
Abstract : Abstract: Enophthalmos caused by orbital volume expansion is the traditional indication for blowout fracture operation, but it may not appear immediately after orbital trauma due to periorbital swelling. The purpose of this study was to investigate the correlations of the orbital volume ratio (OVR) and, orbital fracture area (OFA) with the late enophthalmos measurement in unilateral pure blowout fracture. Seventy-two patients who had experienced a blowout fracture were divided into 2 groups, the conservative treatment group (n = 40) and the operative treatment group (n = 32). The authors measured the preoperative OVR and OFA using three-dimensional facial bone computed tomography and investigated their relationship with late enophthalmos that obtained 6 months after orbital trauma. In both conservative and operative groups, there were significant positive correlations between the OVR and OFA ( P  < 0.05). In the conservative group, both the OVR and OFA showed significant positive correlations with late enophthalmos, but the OVR ( r  = 0.777) was more closely correlated with enophthalmos than the OFA ( r  = 0.739). Quantitative measurements of OVR and OFA are useful parameters that can predict the extent of late enophthalmos and are useful in planning the treatment of blowout fracture.